Temperature-dependent changes of chloride transport kinetics in human red cells - Brahm, J (The Rockefeller University Press, 1977)
Chloride self-exchange in human red cells was studied between 0 degrees C and 38 degrees C. At higher temperatures the flow-tube method was used. Although the general features of chloride transport at 0 degrees C and 38 degrees C are similar, the following differences were found: (a) the maximum pH of chloride self-exchange flux was lowered 0.6 pH unit from 7.8 to 7.2 when temperature was increased from 0 degrees C to 38 degrees C; (b)the apparent half-saturation constant increased from 28 mM at 0 degrees C to 65 mM at 38 degrees C; (c) chloride transport at body temperature is slower than predicted by other investigators by extrapolation from low-temperature results. Chloride transport increased only 200 times when temperature was raised from 0 degrees C to 38 degrees C, because the apparent activation energy decreased from 30 kcal mol(-1) to 20 kcal mol(-1) above a temperature of 15 degrees C; (d) a study of temperature dependence of the slower bromide self-exchange showed that a similar change of activation energy occurred around 25 degrees C. Both in the case of Cl(-) (15 degrees C) and in the case of Br(-) (25 degrees C), critical temperature was reached when the anion self-exchange had a turnover number of about 4x10(9) ions cell (-1)s(-1); (e) inhibition of chloride transport by DIDS (4,4’- diisothiocyano-stilbene-2,2’-disulfonate)revealed that the deflection persisted at 15 degrees C at partial inhibition (66 percent) presumably because DIDS inactivated 66 percent of the transport sites. It is suggested that a less temperature- dependent step of anion exchange becomes rate limiting at the temperature where a critical turnover number is reached.